2021
DOI: 10.1007/s10787-021-00866-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the mucoprotective effects of glycyrrhizic acid-loaded polymeric nanoparticles in a murine model of 5-fluorouracil-induced intestinal mucositis via suppression of inflammatory mediators and oxidative stress

Abstract: Objectives: 5-Flourouracil (5-FU), a chemotherapeutic drug, is linked with severe deteriorating effects on intestine leading to mucositis. Further, Glycyrrhizic acid is a renown herbal medicine with combined mucoprotective, antioxidant and anti-in ammatory actions, however associated with pharmacokinetics limitations. Owing to its remarkable therapeutic action in in ammatory bowel disease inside the polymeric nanocarriers, we have tried to explore its activity against 5-FU led intestinal mucositis. Polymeric n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…We demonstrated that the Candida burden was greatly diminished by the combination, a finding consistent with the higher reduced colonic inflammation. In line with the anti-inflammatory activity of the combination, several components of licorice, including glycyrrhizic acid and isoliquiritigenin, which were detected in our extract, have been reported to have anti-inflammatory, antioxidant and GI tract protective effects ( 40 43 ). Likewise, walnut extract exhibits anti-inflammatory activities through nonchlorogenic and chlorogenic acids known for their antioxidant and anti-inflammatory activities ( 30 , 44 46 ).…”
Section: Discussionsupporting
confidence: 73%
“…We demonstrated that the Candida burden was greatly diminished by the combination, a finding consistent with the higher reduced colonic inflammation. In line with the anti-inflammatory activity of the combination, several components of licorice, including glycyrrhizic acid and isoliquiritigenin, which were detected in our extract, have been reported to have anti-inflammatory, antioxidant and GI tract protective effects ( 40 43 ). Likewise, walnut extract exhibits anti-inflammatory activities through nonchlorogenic and chlorogenic acids known for their antioxidant and anti-inflammatory activities ( 30 , 44 46 ).…”
Section: Discussionsupporting
confidence: 73%
“…These significances consistent abundant other exercises that obtainable substantial upsurge of stomach mucus concentration (PAS) stains nourished several compounds against ethanol produced gastric damages. [48][49][50] PAS stains Figure 2: Effect of the gold nanoparticle using aqueous rhizomes extract of Zingiber officinale on antioxidant enzyme activities (SOD and CAT) and MDA level in the liver. Statistically significant differences were examined using one-way ANOVA and Tukey's post hoc multiple comparisons test.…”
Section: Discussionmentioning
confidence: 99%
“…74,75 Additionally, polymeric NPs can conjugate targeted ligands such as antibodies, peptides, or small molecules specifically binding tissue components or cellular receptors. [76][77][78][79] Recently, various biodegradable polymeric NPs including poly(lactide-co-glycolide) (PLGA), chitosan, dendrimer, and gelatin have been utilized (Fig. 2).…”
Section: Polymeric Npsmentioning
confidence: 99%